Business development strategy analysis at PT Buka Buku Pustaka - Tesar, Mochamad; Indrawan, Raden Dikky; Hannan, Sufrin (International Journal Labs, 2025)
This study examines the business development strategy of PT. Buka Buku Pustaka in the midst of the increasingly stringent challenges of the book industry, including digitization and piracy. The research method used is semi-structural interviews with key sources and secondary data analysis of company documents. The analysis process includes mapping business environmental conditions, SWOT analysis, and the application of the Analytical Hierarchy Process (AHP) method to determine strategy priorities. The results of the study show that the company's strength factors, such as a strong consortium of issuers, play a significant role in strategy development. The proposed strategic priorities include optimizing distribution networks and partnerships with libraries for the Merdeka Learning Program, as well as accelerating the development of e-book infrastructure. This research has implications for PT. Buka Buku Pustaka in creating more effective business strategies and contributing to academic and practical literature on business strategies in the book distribution industry. It is hoped that the results of this research can help companies increase competitiveness and maintain their existence in the digital era.